A BRIEF DESCRIPTION OF COVID-19 PULMONARY VIRAL INFECTION AND REPURPOSING OF DRUGS FOR ITS TREATMENT - PATEL, MANISHA; MAZUMDER, RUPA; KAUSHIK, KAMAL KANT; DEBNATH, ABHIJIT; MISHRA, RAKHI; PAL, SHUBHAM (International Journal of Applied Pharmaceutics, 2022)
A novel coronavirus disease, which is transmitted from human to human has quickly become the cause of the current worldwide health crisis. This virus is, also known as SARS coronavirus, belongs to the Coronaviridae family of viruses. The recent outbreak of acute respiratory disorders starting in Wuhan, China is found to be caused by this virus. The condition caused by it, known as COVID-19 has spread very rapidly all over the world, causing so many death. This led WHO on Mar 11, 2020, to designate it as a global pandemic. An update on the history, etiology, epidemiology, pathophysiology and preventive methods for COVID-19 such as masking, quarantine, and social distancing are discussed in this paper. Repurposed drugs, antibodies, corticosteroids, vaccination and plasma transfusion, are among the treatments explained in the study. Finally, the study discusses India’s COVID vaccination programme. The major aspects of this entire review are to describe COVID-19 infection, its prevention and treatment approach.